High-altitude cerebral oxygen saturation detection using wireless wearable cerebral oximeter - Si, Juanning; He, Yifang; Yao, Junyuan; Yu, Jian; Jing, Rixing; He, Qing; Zhang, Xin; Xiao, Lijun (Frontiers in Neurology, 2024)
Hypobaric hypoxic conditions encountered at high altitudes can significantly impact the physiological functions of human body. Therefore, accurate and real-time monitoring of physiological characteristics is crucial for the prevention of brain injuries in individuals with acute and chronic highaltitude exposure. In this study, a wireless wearable cerebral oximeter (WORTH band) was used for the continuous, real-time monitoring of physiological parameters, including regional cerebral oxygen saturation (rSO2) and heart rate (HR), among subjects with high-altitude exposure. Specifically, during the high-altitude (from 46 m to 4300 m) expedition task, there was a significant decrease in rSO2 accompanied by a corresponding increase in heart rate as the altitude increased. Additionally, during the long-term (52 days) high-altitude (from 356 m to 4658 m) cycling task, the altitudes were significantly correlated with the rSO2 and SpO2 in the elderly subjects. The current findings indicate that the WORTH band oximeter can serve as a promising instrument for measuring rSO2 at high altitudes. We hope that the insights derived from this study could contribute to the management of cerebral oxygenation for individuals with high-altitude exposure and further expand the existing understanding of brain functional detection at high altitudes.